Review of Howley, Howley & Pendarvis - Clifford, Pat (Education Policy Analysis Archives, 1997)
Howley, Craig B., Howley, Aimee & Pendarvis, Edwina D. (1995). Out of Our Minds: Anti-Intellectualism and Talent Development in American Schooling NY, NY: Teachers College Press. Pp. 265; 24.95 (Paper)